Smell fruits selection behavior by a Geoffroy's spider monkey (Ateles geoffroyi) in Quintana Roo, México - Arias-Alzate, Andrés; Zarza, Heliot; Acevedo-Quintero, Juan Fernando (Therya Notes, 2024)
In primates, sensory systems play an important role in the detection and selection of resources. Here, we report a neglected ecological behavior, olfactory fruit selection in a Geoffroy’s spider monkey (Ateles geoffroyi), a primate species found in the Mesoamerican to northern South American region. We directly observed, videotaped, and described a fruits selection behavior using the sense of smell by a free-ranging Geoffroy’s spider monkey during a foraging feeding event in a Manilkara zapota tree, in a tropical semi-evergreen forest area of south of Quintana Roo, México. During the observations, the spider monkey examined the sapodilla (Manilkara zapota) fruits one by one by bringing them close to its nose, apparently allowing it to distinguish between ripe and unripe fruits. Fruits that appeared unripe, were released from the branches without tearing them. Fruits that appeared to be ripe, as the observation suggests, were picked and eaten one at a time. This olfactory-driven selection challenges the common belief that vision, and taste govern food choices. Our findings underscore the vital role of olfaction in frugivore foraging, particularly in discriminating the palatability of cryptic-ripe fruit. This has wider implications for understanding ecosystem interaction networks, encompassing the evolution of distinct odors in fleshy-fruited plant species and the role of sniffing in food discrimination.